BILIMLENDIRIWDI SANLASTÍRÍWDÍŃ ZAMANAGÓY TENDENCIYALARÍ - Saparbaeva, T.T. (SCIENCE and SOCIETY, 2025)
The article analyzes current trends in digitalization within the education system and the integration of modern technologies into the educational process based on global and national experience. The impact of digital tools on the quality of education, student engagement, and teacher competencies is examined from a scientific perspective. Additionally, the necessary conditions and promising directions for the future development of digital pedagogy are explored.